2000
DOI: 10.1086/315705
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal Distending Toxin in Avian and Human Isolates ofHelicobacter pullorum

Abstract: Helicobacter pullorum has been isolated from the feces and livers of poultry and is associated with human gastroenteritis. Discrimination of this organism from other enterohepatic Helicobacter species and Campylobacter species has proven difficult. H. pullorum from both avian and human clinical sources has DNA sequence homology and cytotoxic activity that represent a new member of the cytolethal distending toxin (CDT) family of bacterial toxins. CDT is a potential virulence factor in H. pullorum that may serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 15 publications
0
65
0
1
Order By: Relevance
“…Taxa 2, 3 and 8 are presently unnamed and their taxonomic characterization awaits further study (Dewhirst et al, 2000). Young et al (2000b) have also proposed that the presence/absence of the cdtB gene may prove useful in the classification of microaerobic spiral bacteria. Their suggestion was based on experiments that included eight clinical isolates and three reference strains of H. pullorum.…”
Section: Discussionmentioning
confidence: 99%
“…Taxa 2, 3 and 8 are presently unnamed and their taxonomic characterization awaits further study (Dewhirst et al, 2000). Young et al (2000b) have also proposed that the presence/absence of the cdtB gene may prove useful in the classification of microaerobic spiral bacteria. Their suggestion was based on experiments that included eight clinical isolates and three reference strains of H. pullorum.…”
Section: Discussionmentioning
confidence: 99%
“…Until a few years ago, enteritis caused by these microorganisms were included within those caused by the Campylobacter genus due to their microscopic similarity (86). However, the development of new laboratory techniques as the fatty acid profile (87), mass spectrometry and the PCR (8) have made it possible to identify the germs more specifically.…”
Section: Acute Infectious Gastroenteritismentioning
confidence: 99%
“…Therefore, although the epidemiological chain has not been clearly defined (72), there appears to be a basis to consider food borne transmission of the gastroenteritis of H. pullorum as occurs with the Campylobacter species (4). Generally, they cause watery diarrhea with rectal bleeding in which it is believed that a cytotoxic toxin that has been isolated in certain cases of H. pullorum diarrhea could be involved, although not in other EHHs (86). In our center, where Helicobacter pullorum is being investigated systematically since April 2010, 9 cases that affected patients with a wide age spectrum have been identified (74).…”
Section: Acute Infectious Gastroenteritismentioning
confidence: 99%
“…In infected persons, no history of human contact with birds was reported so far. Nevertheless, recent studies demonstrated that H. pullorum could be an initiator of the intestinal inflammation, because of the releasing cytolethal distending toxin, leading to activation of kB-necrozing factor pathway in the mucous intestine cells [12] . However, Infection of apparently healthy finch and Australian parrots with H. pullorum indicated that these birds might be referred as a source enterohepatic pathogenic bacteria in humans and causing digestive problems to humans.…”
Section: Discussionmentioning
confidence: 99%